Employment Protection and Product Market Regulation - Winfried Koeniger; Andrea Vindigni (Institute for the Study of Labor (IZA), 2003)
Product market regulation and employment protection are highly correlated across OECD countries. Using an augmented model of monopolistic competition we show why in countries with more regulated product markets, incumbent workers prefer to protect jobs relatively more. Product market regulation increases the scope for employment protection because firms can bear the cost of employment protection more easily and still break even. Moreover, product market regulation decreases employment so that the workers' outside option becomes relatively worse. This increases the incentive to protect the job.
Keywords: L16; J65; J63; 330; collective dismissal cost; political economy; Kündigungsschutz; Regulierung; Monopolistischer Wettbewerb; Kündigung; Kosten; Insider-Outsider-Modell; Theorie